Nanoencapsulation of Jania rubens’ Phytochemicals: Antioxidant Properties for Food Applications - R. Maghraby, Yasmin (AUC Knowledge Fountain, 2021)
The development of natural antioxidants that can mitigate oxidation reactions in food products is on the rise. Several antioxidants have been developed from natural terrestrial plants, with less emphasis on marine seaweeds.Rancidity is a major degradative reaction limiting the shelf-life and deteriorating the quality of lipid containing food products. The goal of this study is to evaluate the ability of Jania rubens algal extract encapsulated by chitosan-tripolyphosphate in retarding lipid oxidation reactions in vegetable oils as a food model system. Phytochemicals were extracted from the seaweeds’ matrices by means of an organic solvent. The antioxidant efficacy of the Jania rubens algal extract was evaluated by means of many assays: 2,2-diphenyl-1-picrylhydrazyl, ferric reducing antioxidant power, total phenolic content and total flavonoid content.Bioactive compounds/phytochemicals were further identified using gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry. To improve the Jania rubens’ extract’s efficacy, the phytochemicals were nanoencapsulated into chitosan-tripolyphosphate using the ionic gelation techniques. Box-Behnken design was applied for the optimization of the formulation variables, namely chitosan and tripolyphosphate weights, homogenization time and homogenization speed. The optimum nanoformulation was characterized by transmission electron microscopy. It had a particle size of 161 nm, zeta potential of 31.2 mv, polydispersity index of 0.211 and an entrapment efficiency of 99.7 %. An in-vitro phytochemicals’ release study of the nanoencapsulated extract versus raw extract was performed by means of the dialysis bag diffusion method. This assay was carried out in two stimulation release media to mimic the intestinal and the gastric conditions. In addition, the ability of the optimum formula to extend the shelf-life of vegetable oils, corn, sunflower, soybean and palm oils, was based on peroxide value and thiobarbituric acid assays. Besides, headspace solid-phase microextraction was applied to detect the oils’ volatiles as secondary markers of rancidity. The results revealed that the nanoencapsulated Jania rubens’ extract considerably reduced the rate of formation of the primary and secondary oxidation products in the oils. Finally, it was concluded that the nanoencapsulated extract’s activity was comparable to that of a widely used synthetic antioxidant butylated hydroxytoluene.